Assessment of the Functional Status of Patients after Ischemic Stroke Treated with Thrombolytic Therapy - Danuta Sternal; Ewelina Bąk; Agnieszka Lenart; Bogusława Ryś; Sylwia Krzemińska (Pielęgniarstwo Neurologiczne i Neurochirurgiczne)
Introduction. One of the most effective methods for treating acute ischemic stroke is thrombolytic therapy, which involves intravenous administration of recombinant tissue plasminogen activator (rtPA) within a narrow therapeutic window of up to 4.5 hours from symptom onset.